Influence of Risk Management on Performance: An Empirical Study of International Islamic Bank - Nair, Girish Karunakaran; Purohit, Harsh; Choudhary, Nidhi (International Journal of Economics and Financial Issues, 2014)
Qatar Government is taking active role in promoting its banking sector and International Islamic Bank (IIB) has grown by leaps and bounds since the past decade. Risk Management is becoming a very important aspect in banking industry today and there was a felt need to study its relevance in the context of business performance of IIB. So, this research has primarily focused on the establishment of a link between the various dimensions of risk management with the business performance of IIB. While risk management had seven distinct dimensions, business performance was measured in terms of financial and non-financial performance of the IIB. Based on the contemporary research in risk management, 14 hypotheses were built to link the dimensions of risk management with business performance. The research was undertaken as an empirical study with grounded theory approach. Multiple regression analysis was the method used for establishment of causal relationships between the variables of research interest. The research has developed the mathematical relationships between the research variables of interest. The hypothesis testing has indicated that risk assessment analysis, risk management practices, risk identification, and credit risk assessment are the specific dimensions which influence the business performance. Based on the hypotheses testing results implications are drawn and suggestions are made to the strategic managers of IIB to enhance their business performance. Keywords: Risk management; Risk assessment; Risk analysis; Risk mitigation; Islamic banks. JEL Classifications: G21; G32; G38